Global trends and research patterns in medical surge capacity and response during the Covid-19 pandemic: A bibliometric analysis - de Silva, Heshan Radeesha; Ablakimova, Nurgul; Rachina, Svetlana; Strelkova, Daria; Avdeev, Sergey; Pimenov, Nikolay; Vlasenko, Anna (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: This study aims to analyze global trends and research patterns related to medical surge capacity and response during the Coronavirus Disease 2019 (COVID-19) pandemic through a bibliometric analysis.Methods: The analysis was conducted using data from the Scopus database, focusing on original papers published between 2020 and 2024. Key metrics, including publication trends, geographical distribution, institutional affiliations, and citation statistics, were evaluated. The search was limited to English-language papers.Results: A total of 523 articles were deemed relevant for the analysis. A significant increase in research output was observed during the early stages of the pandemic, with the United States, Canada, and the United Kingdom leading in the number of publications. Major contributors included key institutions such as the University of Toronto, and the Icahn School of Medicine, which represent strong public health research groups. Two Italian authors from the same university, Ragazzoni L. and Della Corte F., were the most prolific in terms of both the number of articles published and citations received. The analysis highlighted the international scope of the research and the willingness of different research groups to collaborate. A shift in research focus was also noted, with keywords moving from immediate pandemic response efforts (human resources, surge capacity) to more specialized topics (machine learning and the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) vaccine).Conclusions: This study provides a comprehensive overview of the global research landscape on medical surge capacity during the COVID-19 pandemic. The findings highlight the critical role of robust public health systems and international collaboration in responding to global health crises.